Postbiotic derived from Bacillus subtilis ACCC 11025 improves growth performance, mortality rate, immunity, and tibia health in broiler chicks - Li, Desheng; Fang, Shan; He, Feng; Fan, Xinyan; Wang, Tieliang; Chen, Zeliang; Wang, Mi (Frontiers in Veterinary Science, 2024)
The objective of this study was to evaluate the effects of dietary supplementation of postbiotics on growth performance, mortality rate, immunity, small intestinal health, tibia characteristics, and hematological parameters of broiler chicks. The postbiotics were derived from Bacillus subtilis ACCC 11025. A total of 480 day-old Arbor acre broiler chicks (52.83 ± 1.38 g) were used in a 42-day study and were randomly allocated into four groups. Each group comprised 6 replicate cages, each containing 20 birds. Dietary treatments were based on a basal diet, supplemented with postbiotics at concentrations of 0.000%, 0.015%, 0.030%, or 0.045%.The results demonstrated an improvement in growth performance, antibody titers against avian influenza virus and Newcastle disease virus, serum albumin levels, and serum total protein levels, as well as a reduction in mortality rate among broiler chicks with increasing levels of postbiotic supplementation. The most significant effect were observed in the group receiving 0.015% postbiotics. Furthermore, a dose-dependent enhancement in tibia weight and tibia weight to length ratio, coupled with a reduction in the robusticity index, was noted.The most favorable outcomes for tibia health were observed in the group receiving 0.030% postbiotics. This improvement in tibia health corresponded to a linear increase in serum calcium and inorganic phosphorus contents. In summary, supplementing broiler chicks with 0.015% postbiotics effectively enhances immunity, leading to improved growth performance and reduced mortality rates. Additionally, a postbiotic dose of 0.030% is suitable for optimizing tibia health.